Public relations programs in special libraries in Quezon City - Duñgo, Liezel Celeste M.; Dizon, Leticia B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
This study investigated the public relations programs of ten special libraries in Quezon City. Specifically, this study: (1) found out the public relations techniques being employed in promoting library collection and services; (2) discovered how much of the total library budget is allocated to public relations programs; (3)determined the library users' opinions on the use of public relations with regard to promoting the library to its actual users and (4) identified the problems related to public relations that are encountered by special librarians.
Library users from ten special libraries were surveyed. The libraries studied were : the College of Evangelical Ministry Library, Department of Agrarian Reform-Bureau of Agrarian Reform Information and Education Library, Department of Education and Natural Resources Library, Local Water Utilities Administration Library, National Power Corporation Library, Philippine Coconut Authority Library, Philippine Information Agency Library, Philippine Nuclear and Research Institute Library, Southeast Asian Ministers and Educators Organization-Innovation Technology (SEAMEO-INNOTECH) Library and the University of the Philippines Institute of Library Science Library.
The questonnaire was the main tool for data gathering. Data gathered were tabulated and analyzed.
The following are the findings of the study: 1. Public relations work in the libraries studied is handled by different departments and personnel. 2. Budget allocation for public relations programs in libraries varied from PHP 50,000 to PHP 1,000 based on only four respondents. 3. The common techniques used for public relations are through publications like annual reports and newsletter; exhibits and dispalys; library posters; friends of the library; presentations to community groups; library logo; participation of librarians in professional organizations. 4. Booklists were found to be the most effective public relations technique and library guides and handbooks are the least effective.
Based on the data gathered, the following conclusions were made: 1. Many of the special libraries in Quezon City have no formal public relations program. 2. Generally, there seems to be little financial support for library public relations programs. 3. There is a lack or absence of library personnel to handle public relations work. 4. The person that is usually involved in public relations work is the chief librarian.
The following recommendations were made: 1. Public relations programs in special libraries must be formalized. There should also be a distinct public relations unit within the library with adequate staff to handle public relations work and competent budgetary allocation. 2. If a library cannot afford to have a full-time public relations staff, much effort must be spent to improve the public relations techniques and tools used to communicate with the target audience. 3. Any formal public relations program should include a monitoring and evaluation component in order to determine program effectiveness. 4. In planning a public relations program, management should develop a good library collection and work on items which need to be developed. 5. Since special libraries have a defined clientele, the most appropriate technique(s) in getting the attention of the users should be used. 6. It is important, of course, for the special libraries to have a statement of goals and objectives and a plan of action be they long or short-term. In doing so, it would be easier for the libraries to get financial support from the administration.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public relations -- Libraries -- Philippines -- Quezon City; Special libraries -- Philippines -- Quezon City